State-Owned Enterprises As Development Agent: Between Business Interests And Social Responsibility - Sonny Setyadhy; Adie Kusna Wibowo (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the dual role of State-Owned Enterprises (SOEs) as business entities and agents of national development. The study analyzes how SOEs balance profit orientation with social responsibility in carrying out their function as a state instrument in economic development. Through a literature review approach and document analysis of several SOEs in Indonesia, the research reveals the dynamic relationship between commercial objectives and social missions. The results indicate that SOEs face dilemmas in balancing business efficiency with the public service obligations, while corporate governance emerges as a key factor in optimizing both roles. The research concludes that clear regulatory frameworks and effective monitoring mechanisms are necessary to ensure SOEs can optimally fulfill their dual fuctions.